Treating Religious Differences: Hikmah Muta’aliyah as An Alternative to Ethical Crisis in Contemporary Era - Nurul Khair; Muhammad Thaha (IAIN Palangka Raya, 2020)
Religion is a belief system that regulates all the behavior of its adherents to realize relationships between humans in social context through spiritual values that always direct humans to will and act based on goodness by involving the analysis of reason to determine good and bad in accordance to religious orders, that each individual can avoid lust and emotions in him that describe animal behavior. Inevitably, individuals different from animal behaviors depict spiritual values in belief system trying to humanize each individuals. However, people's behavior in religious belief system in the contemporeries did not match the facts of reality. Because, every religious community creates an inclusive attitude among the various adherents of religions based on the narrow perception of humans to address differences in social contexts. As a result, every individual sees behaviors of other groups as something bad, they must be destroyed in the social environment. In order to overcome the problems that occur within the scope of religious communities, this paper aims to examine the Hikmah Muta’aliyah of Mulla Sadra to understand the behavior of religious adherents and provide solutions to ethical crises in this Contemporary time by using qualitative methodology resulting in the conclusion that the Hikmah Muta’aliyah of Mulla Sadra emphasizes the perception of reasons in presenting universal knowledge, that each individual can think openly to respond variety of differences. Accomodative thinking will create values of tolerance and humanity in the contexts of religion, that each individual can build harmonious relationship between fellow humans.Keyword : Religion, Behavior, Hikmah Muta’aliyah